Cardiac rehabilitation in the Comprehensive Cardiac Care program in the time of a COVID – 19 pandemic - Stawikowski, Cezary; Zielonka, Bartłomiej; Kowalczyk, Ilona; Stachyra, Bartłomiej; Wolanin, Marta; Osińska, Aleksandra; Wolanin, Izabela; Krawiec, Paulina; Madej, Karolina; Dengler, Barbara (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Cardiac rehabilitation in patients after myocardial infarction is an established form of therapy. Its main tasks in the context of the implementation of the KOS program are to improve quality of life, consolidate the effects of hospital treatment and ensure better functioning after a cardiovascular incident. The purpose of this paper is to analyze the current level of knowledge regarding cardiac rehabilitation of patients during the COVID-19 pandemic. Description of the state of knowledge: COVID-19 poses a significant threat to patients with cardiovascular disease. Physiotherapy in the Cardiac Rehabilitation Unit involves a step-by-step, individualized rehabilitation plan in accordance with the patient’s condition. An important tool for clinical evaluation is capacity tests, the results of which provide key information for the rehabilitation team in selecting exercise intensity. These tests are performed on the first and last days of rehabilitation. In Polish conditions, the most common tests examining capacity are an exercise test on a treadmill or bicycle cycler or a 6-minute walk test. Due to the diversion of a significant number of specialists and health care teams to treat COVID - 19 patients, access to the possibility of implementing the various stages of the Coordinated Specialized Care program after myocardial infarction has been limited. Summary: Post-infection patients are often forced to live a sparing lifestyle. They show reduced exercise tolerance and easier fatigability. With these aspects in mind, improving the quality of life of patients after cardiovascular incidents in the era of the pandemic requires even greater involvement of the entire rehabilitation team.